Great boast, small roast on effects of selective serotonin reuptake inhibitors: Response to a critique of our systematic review - Katakam, Kiran Kumar; Sethi, Naqash Javaid; Jakobsen, Janus Christian; Gluud, Christian (Acta Neuropsychiatrica, 2018)
Our systematic review in BMC Psychiatry (see record [rid]2017-06469-001[/rid]) concluded that selective serotonin reuptake inhibitors (SSRIs) compared with placebo significantly increase the risk of serious adverse events (SAEs) in patients with major depression and the potential beneficial effects of SSRIs seem to be outweighed by the harms. Hieronymus et al. accused us of methodological inaccuracies and blatant errors. In their post-hoc analysis of our data, they reported that SSRIs only increase the risk of SAEs in elderly and seems safe for non-elderly patients. They also found our review misleading because our efficacy analyses were based on the 17-item Hamilton Depression Rating Scale; we included suboptimal SSRI doses; and we missed some ‘pivotal trials’. We do not agree with Hieronymus et al. regarding several of the ‘errors’ they claim that we have made. However, we acknowledge that they have identified minor errors and that we missed some trials. After rectifying the errors and inclusion of the missed trials by us and Hieronymus et al., we re-analysed the data. The updated analyses are even more robust and confirm our earlier conclusions. SSRIs significantly increase the risk of an SAE both in non-elderly (p = 0.045) and elderly (p = 0.01) patients [overall odds ratio 1.39; 95% confidence interval (CI) 1.13 to 1.73; p = 0.002; I² = 0%]. Moreover, SSRIs did not change noticeably the 17-item Hamilton Depression Rating Scale, the internationally accepted scale (mean difference −2.02 points; 95% CI −2.38 to −1.66; p < 0.00001). We found no differential effect of dose (p = 0.20). (PsycINFO Database Record (c) 2018 APA, all rights reserved)
Keywords: Depression; Drug Therapy; Major Depression; Placebo; SSRI; Serotonin Reuptake Inhibitors; Systematic review